Forms, Models and Mechanisms of Public-Private Partnerships in the Service Sector - Utemuratova Gulnarakhan Khojaniyazovna, (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
In this article, the forms of public-private partnership, the main directions of economic activity between state and private business entities, the economic content, goals and objectives, structure and models of the "public-private partnership" category, implementation of public-private partnership projects, its advantages, service provision the main forms of public-private partnership, the main features of this system, the role of public-private partnership in the system of interaction between the public and private sectors and its differences from outsourcing of public services and state franchising have been researched.